2018
DOI: 10.1155/2018/8178305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lime, Vermicompost, and Chemical P Fertilizer on Selected Properties of Acid Soils of Ebantu District, Western Highlands of Ethiopia

Abstract: Soil acidity is one of the major factors limiting soil fertility and crop production in large areas of Ethiopia. A two-month incubation experiment was conducted to evaluate the effects of lime, vermicompost (VC), and chemical phosphorus (P) fertilizer on selected chemical properties of Dystric Nitisols in Ebantu District, Western Ethiopia. The treatments comprised of three rates of lime (2, 4, and 6 tons CaCO3·ha−1), VC (2.5, 5, and 7.5 tons·ha−1), and mineral P fertilizer (20, 40, and 60 kg·P·ha−1) each appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 24 publications
6
46
0
1
Order By: Relevance
“…Related to soil acidity attributes vermicompost also had respectable response as reported by Wael et al (2011) stated that vermicompost was used to increase the pH in acidic soils and reduce Al and Mn toxicity because of its alkalinity. Study in the western Ethiopia acidic soil showed that Vermicompost application at different application rate had gave significant effects (Abdissa et al, 2018), on soil acidity features like soil pH, exchangeable acidity and soil acid saturation percentage which was positively affected like other soil physicochemical properties due to application of vermicompost which was prepared from most preferred raw materials.…”
Section: Vermicompost As Acid Soil Amendmentmentioning
confidence: 99%
“…Related to soil acidity attributes vermicompost also had respectable response as reported by Wael et al (2011) stated that vermicompost was used to increase the pH in acidic soils and reduce Al and Mn toxicity because of its alkalinity. Study in the western Ethiopia acidic soil showed that Vermicompost application at different application rate had gave significant effects (Abdissa et al, 2018), on soil acidity features like soil pH, exchangeable acidity and soil acid saturation percentage which was positively affected like other soil physicochemical properties due to application of vermicompost which was prepared from most preferred raw materials.…”
Section: Vermicompost As Acid Soil Amendmentmentioning
confidence: 99%
“…The effective cation exchange capacity of the soil was significantly affected by all treatments except the chemical P fertilizers when applied at the rate of 40 and 60 kg ha -1 . The increase was due to improved soil condition by vermicompost and lime and increase of negative charges on the surface of the soil colloids (Bekela et al, 2018) [3] . Mahmoud and Ibrahim (2012) [21] reported that CEC was increased significantly with the application of vermicompost alone and it's in combination with water treated residue.…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
“…Phosphorus is the most yield-limiting plant nutrient in many regions of the world [5,6], tropical Africa [7], and most Ethiopian soils [8,9]. e forms of P greatly influence its availability in the soil and subsequently influence productivity [10].…”
Section: Introductionmentioning
confidence: 99%